Prevalence and phenotype associations of complement factor I mutations in geographic atrophy. Issue 9 (29th June 2021) - Khan, Adnan H.; Sutton, Janice; Cree, Angela J.; Khandhadia, Samir; De Salvo, Gabriella; Tobin, John; Prakash, Priya; Arora, Rashi; Amoaku, Winfried; Charbel Issa, Peter; MacLaren, Robert E.; Bishop, Paul N.; et al.
Abstract: Rare variants in the complement factor I ( CFI ) gene, associated with low serum factor I (FI) levels, are strong risk factors for developing the advanced stages of age‐related macular degeneration (AMD). No studies have been undertaken on the prevalence of disease‐causing CFI mutations in patients with geographic atrophy (GA) secondary to AMD. A multicenter, cross‐sectional, noninterventional study was undertaken to identify the prevalence of pathogenic rare CFI gene variants in an unselected cohort of patients with GA and low FI levels. A genotype‐phenotype study was performed. Four hundred and sixty‐eight patients with GA secondary to AMD were recruited to the study, and 19.4% ( n = 91) demonstrated a low serum FI concentration (below 15.6 μg/ml). CFI gene sequencing on these patients resulted in the detection of rare CFI variants in 4.7% ( n = 22) of recruited patients. The prevalence of CFI variants in patients with low serum FI levels and GA was 25%. Of the total patients recruited, 3.2% ( n = 15) expressed a CFI variant classified as pathogenic or likely pathogenic. The presence of reticular pseudodrusen was detected in all patients with pathogenic CFI gene variants. Patients with pathogenic CFI gene variants and low serum FI levels might be suitable for FI supplementation in therapeutic trials. Abstract : This study demonstrates, for the first time, the prevalence of disease‐causing complement factor I (CFI) gene mutations in an unselected cohort of patients with geographic atrophy secondary to age‐related macular degeneration. Reticular pseudodrusen was detected in all patients with a rare CFI gene variant in this study.